2019
DOI: 10.1016/j.jchromb.2019.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PK11195 concentrations in rodent whole blood and tissue samples by rapid and reproducible chromatographic method to support target-occupancy PET studies

Abstract: In Positron Emission Tomography (PET) research, it is important to assess not only pharmacokinetics of a radiotracer in vivo , but also of the drugs used in blocking/displacement PET studies. Typically, pharmacokinetic/pharmacodynamic (PK/PD) analyses of drugs used in rodent PET studies are based on population average pharmacokinetic profiles of the drugs due to limited blood volume withdrawal while simultaneously maintaining physiological homeostasis. This likely results in bias of PET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Therefore, further validation in in vivo and large animal studies is required to account for the extent and substrate utilization changes in the working heart. A single concentration of PK11195 was employed based on prior studies (Stadulyte et al, 2019) and thus it is unknown whether different concentrations would have greater or lesser effects. Several reports indicate that PK11195 can affect lipid fluidity of mitochondrial outer membrane, and, therefore, can potentially affect the function of other proteins in OMM (Miccoli et al, 1999;Hatty et al, 2014) or even directly inhibit the OSCP subunit of F 0 F 1 -ATP synthase (Cleary et al, 2007;Krestinina et al, 2009) which is reported to form mPTP (Alavian et al, 2014;Mnatsakanyan et al, 2019;Bernardi, 2020).…”
Section: Limitationsmentioning
confidence: 99%
“…Therefore, further validation in in vivo and large animal studies is required to account for the extent and substrate utilization changes in the working heart. A single concentration of PK11195 was employed based on prior studies (Stadulyte et al, 2019) and thus it is unknown whether different concentrations would have greater or lesser effects. Several reports indicate that PK11195 can affect lipid fluidity of mitochondrial outer membrane, and, therefore, can potentially affect the function of other proteins in OMM (Miccoli et al, 1999;Hatty et al, 2014) or even directly inhibit the OSCP subunit of F 0 F 1 -ATP synthase (Cleary et al, 2007;Krestinina et al, 2009) which is reported to form mPTP (Alavian et al, 2014;Mnatsakanyan et al, 2019;Bernardi, 2020).…”
Section: Limitationsmentioning
confidence: 99%